Oxygen Vacancies in Oxide Nanoclusters: When Silica Is More Reducible Than Titania - Cuko, Andi; Bromley, Stefan T.; Calatayud, Monica (Frontiers in Chemistry, 2019)
Oxygen vacancies are related to specific optical, conductivity and magnetic properties in macroscopic SiO2 and TiO2 compounds. As such, the ease with which oxygen vacancies form often determines the application potential of these materials in many technological fields. However, little is known about the role of oxygen vacancies in nanosized materials. In this work we compute the energies to create oxygen vacancies in highly stable nanoclusters of (TiO2)N, (SiO2)N, and mixed (TixSi1−xO2)N for sizes between N = 2 and N = 24 units. Contrary to the results for bulk and surfaces, we predict that removing an oxygen atom from global minima silica clusters is energetically more favorable than from the respective titania species. This unexpected chemical behavior is clearly linked to the inherent presence of terminal unsaturated oxygens at these nanoscale systems. In order to fully characterize our findings, we provide an extensive set of descriptors (oxygen vacancy formation energy, electron localization, density of states, relaxation energy, and geometry) that can be used to compare our results with those for other compositions and sizes. Our results will help in the search of novel nanomaterials for technological and scientific applications such as heterogeneous catalysis, electronics, and cluster chemistry.